Estudos químicos e anatômicos de cascas de clones de Eucalyptus - Sartori, Caroline Junqueira (2016)
The barks generated from the wood processing industries are wastes generated in significant quantities, becoming interesting to have basic studies of their anatomical and chemical properties in order to make better use of this material. This study aimed to carry out anatomical studies, chemical and tannins from the barks of commercial clones of Eucalyptus. For this, permanent histological slides for anatomical characterization and percentage of cellular elements were prepared; and cellular elements were dissociated for biometry of the elements. The analyses were related to chemical extractives, ash, lignin, suberin, sugars, phenols, tannins, flavonoids and antioxidant activity of the extracts. The tannins were extracted in pure water and with water mixed with sodium sulfite, and were subsequently evaluated the properties by FT-IR. It was verified by the anatomical characterization and chemical quantification, the similarity between the clones. Regarding the biometrics of cellular elements, statistically significant differences were not observed for the following parameters: length and diameter of sieve tube, axial parenchyma diameter, and rays hight. The yield of condensed tannins and Stiasny index for studied clones are low, showing the infeasibility of using bark for the extraction of tannins to produce adhesives, however tannins and other bioactive phenolic compounds can be used in the pharmaceutical and cosmetics sectors due to its antioxidant potential. The spectrum of tannins is the same as the one found the literature. Due to the high yield of verified sugar, (around 46,68%) sugars are potencial products, with a high yield of glucose , it is interesting for application in biorefinery.